Pentecostal modernism Lovecraft, Los Angeles, and world-systems culture - Shapiro, Stephen 1964-; Barnard, Philip 1951- (New directions in religion and literature, 2017)
"Bringing together new accounts of the pulp horror writings of H.P. Lovecraft and the rise of the popular early 20th-century religious movements of American Pentecostalism and Social Gospel, Pentecostal Modernism challenges traditional histories of modernism as a secular avant-garde movement based in capital cities such as London or Paris. Disrupting accounts that separate religion from progressive social movements and mass culture, Stephen Shapiro and Philip Barnard construct a new Modernism belonging to a history of regional cities, new urban areas powered by the hopes and frustrations of recently urbanized populations seeking a better life. In this way, Pentecostal Modernism shows how this process of urbanization generates new cultural practices including the invention of religious traditions and mass-cultural forms."--Bloomsbury Publishing